2022
DOI: 10.1155/2022/8223903
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Associated Factors of Postoperative Pulmonary Complications after Abdominal Surgery in the Public Hospital, Addis Ababa, Ethiopia

Abstract: Background. Postoperative pulmonary complications are a wide variety of disorders that affect normal respiratory functions, which in turn lead to morbidity and mortality. The extent to which it occurs is not yet studied in most clinical settings. This study assessed the incidence and risk factors of postoperative pulmonary complications in patients undergoing abdominal surgery under general anesthesia. Methods. A multicenter, prospective cross-sectional study was conducted at Menelik II, Tikur Anbessa Speciali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(46 reference statements)
3
1
0
Order By: Relevance
“…Our study revealed that the risk of developing PPC was higher in patients with a postoperative albumin level less than 3.5 g/dl compared to those with a postoperative albumin level greater than 3.5 g/dl. This finding was in agreement with other studies ( 24 , 34 ). This could be due to a low blood protein level, which results in vascular endothelial dysfunction, or by reducing colloid osmotic pressure.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our study revealed that the risk of developing PPC was higher in patients with a postoperative albumin level less than 3.5 g/dl compared to those with a postoperative albumin level greater than 3.5 g/dl. This finding was in agreement with other studies ( 24 , 34 ). This could be due to a low blood protein level, which results in vascular endothelial dysfunction, or by reducing colloid osmotic pressure.…”
Section: Discussionsupporting
confidence: 94%
“…The reasons may be that the prolonged operation duration means prolonged anesthesia time that depresses movements of inter-costal muscles, alters the shape and motion of the chest wall, and diminishes ribcage excursion, affecting lung mechanics and resulting in a decrease in functional residual capacity ( 35 ). In our study, patients with prolonged surgical times were more likely to develop PPC than those whose surgeries lasted less than 2 h, which was consistent with previous studies ( 27 , 31 , 34 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Treatment and prognosis depends on the location of the tumor, its stage and the type of cancer cell. 2 Postoperative respiratory complications are frequent events that occur in high-risk patients.…”
Section: Introductionmentioning
confidence: 99%